Cloning of a higher-plant plastid omega-6 fatty acid desaturase cDNA and its expression in a cyanobacterium. - Hitz, W D (1994)
Oligomers based on amino acids conserved between known plant omega-3 and cyanobacterium omega-6 fatty acid desaturases were used to screen an Arabidopsis cDNA library for related sequences. An identified clone encoding a novel desaturase-like polypeptide was used to isolate its homologs from Glycine max and Brassica napus. The plant deduced amino acid sequences showed less than 27% similarity to known plant omega-6 and omega-3 desaturases but more than 48% similarity to cyanobacterial omega-6 desaturase, and they contained putative plastid transit sequences. Thus, we deduce that the plant cDNAs encode the plastid omega-6 desaturase. The identity was supported by expression of the B. napus cDNA in cyanobacterium. Synechococcus transformed with a chimeric gene that contains a prokaryotic promoter fused to the rapeseed cDNA encoding all but the first 73 amino acids partially converted its oleic acid fatty acid to linoleic acid, and the 16:1(9c) fatty acid was converted primarily to 16:2(9c, 12) in vivo. Thus, the plant omega-6 desaturase, which utilizes 16:1(7c) in plants, can utilize 16:1(9c) in the cyanobacterium. The plastid and cytosolic homologs of plant omega-6 desaturases are much more distantly related than those of omega-3 desaturases.